2014
DOI: 10.1016/j.infbeh.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Social looking, social referencing and humor perception in 6- and-12-month-old infants

Abstract: Social referencing refers to infants' use of caregivers as emotional referents in ambiguous situations (Walden, 1993). Studies of social referencing typically require ambulation, thereby over-looking younger, non-ambulatory infants (i.e., ≤ 8-mos) and resulting in a widespread assumption that young infants do not employ this strategy. Using a novel approach that does not require mobility, we found that when parents provided unsolicited affective cues during an ambiguous-absurd (i.e., humorous) event, 6-month-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 33 publications
0
54
0
4
Order By: Relevance
“…Finally, humor requires sharing something interpersonal, focusing one's attention on both a social partner and the object of the humorous episode. Mireault et al (2014) found that six-month-olds smiled and laughed at an absurd event compared to an ordinary event, even when their parents remained affectively neutral. However, when their parents also smiled and laughed at the event, infants increased their positive response to it.…”
Section: Why Does Humor Arise So Early?mentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, humor requires sharing something interpersonal, focusing one's attention on both a social partner and the object of the humorous episode. Mireault et al (2014) found that six-month-olds smiled and laughed at an absurd event compared to an ordinary event, even when their parents remained affectively neutral. However, when their parents also smiled and laughed at the event, infants increased their positive response to it.…”
Section: Why Does Humor Arise So Early?mentioning
confidence: 95%
“…In a longitudinal study of infant humor perception from three-to six-months, Mireault et al (2012) found that the majority of the time when acting absurdly to amuse their babies, parents also provided humor cues, both communicating and sharing positive affect. Follow-up studies with five-and six-month-olds found that although they are able to independently appraise an event as funny, they smile and laugh more at the event if their parents do as well (Mireault et al 2014. Interestingly, by 7-months, infants refrained from laughing at an event they had found amusing at 5-and 6-months of age if their mothers-who were performing the event-did not laugh.…”
Section: Humor As Fundamentally Socialmentioning
confidence: 99%
“…Until recently, researchers had not investigated whether younger infants also engage in social referencing, in large part because younger infants are not mobile and so could not be put to classic tests of social referencing (Walden et al 2007). However, it is possible that a similar mechanism is in place in early humorous interactions and that parents provide affective cues that guide infants' interpretation of what are initially ambiguous behaviors (Mireault et al 2014).…”
Section: Parents As a Frame Of (Social) Referencingmentioning
confidence: 99%
“…Following Reddy (2008)'s assertion that even tickling requires a "social wrapping" to define a stimulus as funny (p. 201), Mireault et al (2014) investigated social referencing among six-month-old infants using humorous instead of threatening events. Although six-month-olds found absurd events funny all on their own and therefore did not need to reference parents, they paid close attention to parental humor cues, shifting their gaze from the event to their parent and back such that parental affect was as salient as the event itself (Mireault et al 2014).…”
Section: Parents As a Frame Of (Social) Referencingmentioning
confidence: 99%
See 1 more Smart Citation